Needs assessment for health service design for people with back pain in a hospital setting: A qualitative study. (11th February 2022) - Gorgon, Edward; Maka, Katherine; Kam, Andrew; Nisbet, Gillian; Sullivan, Justin; Regan, Gerard; Pourkazemi, Fereshteh; Lin, Jianhua; Mohamed, Mahmoud; Leaver, Andrew
Abstract: Background: There is a need for effective health service solutions to provide greater structure and support for implementing evidence‐based practice in back pain care. Patient involvement in developing these solutions is crucial to increase relevance, acceptability and uptake. Objectives: To determine patients' perceived needs and barriers to best‐practice back pain care, and potential solutions to better address care needs. The study is the third in a series of needs assessment studies feeding into the 'idea generation' for service design in a large teaching hospital in a culturally and linguistically diverse community in metropolitan Sydney, Australia. Design: We conducted a combination of focus groups and in‐depth interviews using an interpretive description approach. We used inductive thematic analysis to identify the main themes. Setting and Participants: We purposively sampled patients with diverse characteristics from the neurosurgery and physiotherapy outpatient clinics, in particular those whose primary language was English, Arabic, Persian or Mandarin. Non‐English audio recordings were translated and transcribed by bilingual researchers. Results: There were 24 participants (focus groups = 9; individual interviews = 15) when data saturation was reached. The analysis identified three key themes with several subthemes around what service designers needed to understand in helping people with back pain in this setting: (1) This is who I am ; (2) It's not working for me ; and (3) What I think I need . Discussion and Conclusion: This study highlights that perceived unmet needs of patients are underpinned by unhelpful beliefs about the causes of and solutions for back pain, misaligned care expectations, unclear expectations of the hospital role and fragmentations in the health system. To design and implement a service that can deliver better back pain care, several solutions need to be integrated around: developing new resources that challenge unhelpful beliefs and set realistic expectations; improving access to education and self‐management resources; focusing on individualized care; using a collaborative multidisciplinary approach within the hospital; and better connecting with and directing primary health care services. Patient or Public Contribution: A consumer representative of the Western Sydney Local Health District provided input during study conceptualisation and is duly recognized in the Acknowledgements section.